1997
DOI: 10.1074/jbc.272.27.16999
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Stimulating Protein (MSP) Binds to Its Receptor via the MSP β Chain

Abstract: Macrophage stimulating protein (MSP)1 was originally purified from human plasma, based on its activity for murine resident peritoneal macrophages (1). It is a 78-kDa heterodimeric protein composed of a disulfide-linked 53-kDa ␣ chain and a 25-kDa ␤ chain (calculated from amino acid composition). The ␣ chain contains a N-terminal hairpin loop followed by four kringle domains. The ␤ chain has a serine protease-like domain but is devoid of enzymatic activity due to amino acid substitutions in the catalytic triad.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 34 publications
(43 reference statements)
4
57
1
Order By: Relevance
“…Macrophages respond to MSP-1 via RON activation, leading to changes in cell shape and increased migration, as well as an inhibition of nitric oxide production (23)(24)(25). We found that primary mouse peritoneal macrophages, but not primary mouse bone marrow macrophages, underwent a characteristic shape change upon activation by MSP-1 ( Fig.…”
Section: Msp-1 Activation By Mt-sp1 Results In Macrophage Morphologymentioning
confidence: 69%
See 1 more Smart Citation
“…Macrophages respond to MSP-1 via RON activation, leading to changes in cell shape and increased migration, as well as an inhibition of nitric oxide production (23)(24)(25). We found that primary mouse peritoneal macrophages, but not primary mouse bone marrow macrophages, underwent a characteristic shape change upon activation by MSP-1 ( Fig.…”
Section: Msp-1 Activation By Mt-sp1 Results In Macrophage Morphologymentioning
confidence: 69%
“…We found that primary mouse peritoneal macrophages, but not primary mouse bone marrow macrophages, underwent a characteristic shape change upon activation by MSP-1 ( Fig. 3) (25). The effects of the endogenous MT-SP1 inhibitor, HAI-1, and a highly specific MT-SP1 antibody inhibitor (Fig.…”
Section: Msp-1 Activation By Mt-sp1 Results In Macrophage Morphologymentioning
confidence: 99%
“…The response to HGF and MSP through the activation of Met and Ron is mediated by the same pathways, mainly by Ras and by PI-3 Kinase (Wang et al, 1996;Bardelli et al, 1999). Met can regulate growth and transformation by activating the MAP kinase cascade through Grb2/Sos/Ras complex whereas the Ron pathway is directed more towards cellular movement and matrix invasion (Santoro et al, 1996;Wang et al, 1997). When Met and Ron receptors are co-expressed, the formation of heterodimers may balance the activation of Ras and PI-3 kinase pathways.…”
Section: Discussionmentioning
confidence: 99%
“…1B), and both ligands belong to the plasminogen-like growth factor family (31). Circulating MSP is synthesized in liver cells as a single-chain precursor (pro-MSP) that does not bind to RON (32,33). Under cellular stress, pro-MSP undergoes proteolytic maturation to become a disulfide-linked MSP␣␤, which binds and activates RON (33).…”
mentioning
confidence: 99%
“…Circulating MSP is synthesized in liver cells as a single-chain precursor (pro-MSP) that does not bind to RON (32,33). Under cellular stress, pro-MSP undergoes proteolytic maturation to become a disulfide-linked MSP␣␤, which binds and activates RON (33). Several serine proteases (kallikreins, matriptase, hepsin, and human airway trypsin-like protease) recognize the cleavage site (Arg 483 -Val 484 ) between the K 4 and SP domains (33).…”
mentioning
confidence: 99%